VISCOELASTIC EQUATION WITH LOCALLY DISTRIBUTED DAMPING - Perez Salvatierra, Alfonso (2012)
In this present work we study the one-dimensional viscoelastic equation defined on the interval [0, L]. We divided the study into two parts: In the first we analyze the existence and uniqueness of solutions using the theory of the linear semigroups, applying in the Abstract Cauchy problem and in the second part we see the exponential stability of the C0-semigroup of contractions associated with linear viscoelastic system.